Synthesis of polymer microsphere‐supported chiral pyrrolidine catalysts by precipitation polymerization and their application to asymmetric Michael addition reactions. Issue 11 (28th April 2021) - Debnath, Mithun Kumar; Oyama, Wako; Ono, Yuya; Sugimoto, Takuya; Watanabe, Rina; Haraguchi, Naoki
Abstract: Polymer microsphere‐supported chiral pyrrolidine catalysts were successfully synthesized by a precipitation polymerization incorporating a methacrylate monomer bearing chiral N ‐Boc‐pyrrolidine moiety, followed by removal of the N ‐Boc groups. The resulting polymeric catalysts were applied to the asymmetric Michael addition reactions of aldehydes with alkyl vinyl ketones. The effects of the comonomer, the molar ratios within the catalyst, the catalyst loading, the temperature, and the solvent on the catalytic performance were investigated in detail. The reactions were found to proceed smoothly in the absence of a solvent. A hydrophobic polystyrene‐based chiral pyrrolidine catalyst exhibited high reactivity (up to 97% yield) and enantioselectivity (up to 95% ee) during these reactions. The catalyst could also be recovered and reused up to five times without significant loss of activity. Abstract :